Palm trees limit the proliferation of lianas in the forests of the Amazon-Cerrado-Pantanal ecotone (Research, Society and Development, 2021)
Palm trees have structural characteristics that limit their colonization by lianas (e.g., rapid growth, flexible monopodial stem and deciduous leaves). The objective of our study was to evaluate whether the presence of palm trees can influence the plant infestation by lianas in three forest communities (FG, FS1 and FS2) of the Estação Ecológica da Serra das Araras (EESA), the only transition space between three biomes in Brazilian territory. In each forest we allocate a permanent plot of 1 ha, sampling trees and palm trees with DBH ≥ 10 cm, assigning a binary classification as to the presence or absence of vines in individuals, as well as calculating the average rates of infestation by lianas and occupation by palm trees. In all, we registered 1,557 individuals, distributed in 41 families and 147 species. We counted 682 infested plants and 875 free of lianas in a total of 1,063 trees and 494 palms, with 73% of the infested plants being trees. The presence of palm trees limited the proliferation of lianas in our areas. Trees were more vulnerable to liana infestation than palm trees and the favorable condition for their massive colonization was that in which the palm occupation rate reached 23% per hectare. We found that the way of life substantially influences plant infestation in the Amazon-Cerrado-Pantanal ecotone, being the largest infestation observed among low trees. We conclude that the rate of infestation tends to decrease due to the increase in the density of palm trees.